The state of the field for research on agrifood systems - Porciello, Jaron; Skidan, Volha; Ambikapathi, Ramya; Boonabaana, Brenda; Guerra, Jill; Lidder, Preetmoninder; Piñeiro, Valeria; Phillips, Lauren; Savilaakso, Sini; Schuster, Monica; Sheikh, Hafsa; Tufan, Hale; et al. (CAB International, 2024)
‘The State of the Field for Research on Agrifood Systems’ uses artificial intelligence (AI) to analyse global research distribution from the past 13 years. This report provides a macro-level review of more than six million summaries of scientific papers and reports. It offers a snapshot across agrifood systems research, highlighting where progress has occurred, and where significant gaps remain. Despite 60% growth in research publications across agrifood systems in the past 13 years, there are extremely low levels of scientific research targeting the poorest, hungriest, and most vulnerable to climate change countries. Resolving this requires a systems approach and challenging long-standing norms regarding power dynamics across science and policy, including publication and funding norms.